Selecting a multiplex PCR panel for accurate molecular diagnosis of intestinal protists: a comparative study of Allplex® (Seegene®), G-DiaParaTrio (Diagenode®), and RIDA®GENE (R-Biopharm®) assays and microscopic examination - Argy Nicolas; Nourrisson Céline; Aboubacar Ahmed; Poirier Philippe; Valot Stéphane; Laude Adrien; Desoubeaux Guillaume; Pomares Christelle; Machouart Marie; Le Govic Yohann; Dalle Frédéric; Botterel Françoise; et al. (Parasite, 2022)
Commercial multiplex PCR assay panels were developed to overcome the limitations of microscopic examination for parasitological diagnosis on stool samples. However, given the increased supply of this diagnostic approach, these assays must be evaluated to position them in a diagnostic algorithm. Analytical performances of the multiplex PCR assay G-DiaParaTrio, Allplex® GI parasite and RIDA®GENE parasitic stool panel for detecting Blastocystis sp., Entamoeba histolytica, Giardia duodenalis, Cryptosporidium spp., Dientamoeba fragilis, and Cyclospora cayetanensis, were assessed through a retrospective comparative study on 184 stool samples initially sent for parasitological investigation. The composite reference method for parasitological diagnosis was microscopic observation and Entamoeba histolytica-specific adhesion detection when necessary. Multiplex PCR assays were performed on extracted DNA from each stool, following the manufacturer’s recommendations. Discrepant results with the composite reference method were investigated with species-specific PCR to approach a final parasitological diagnosis. Overall sensitivity/specificity for the multiplex PCR assays was 93.2%/100% for G-DiaParaTrio, 96.5%/98.3% for Allplex® GI parasite and 89.6%/98.3% for RIDA®GENE, whereas the composite reference method presented an overall sensitivity/specificity of 59.6%/99.8%. These results confirmed the added diagnostic value of the multiplex PCR approach for gastrointestinal protists. Nevertheless, the PCR procedure and the analytical performance for each protist of interest, variable depending on the multiplex PCR assay, must be considered when implementing a PCR-based diagnostic approach.